Male hypogonadism: 14‐year prospective outcome in 550 men with type 2 diabetes. Issue 3 (27th March 2019) - Malipatil, Nagaraj S.; Yadegarfar, Ghasem; Lunt, Mark; Keevil, Brian; Siddals, Kirk; Livingston, Mark; Roberts, Siriol; Narayanan, Prakash; Rutter, Martin; Gibson, J. Martin; Donn, Rachelle; Hackett, Geoff; et al.
Summary: Introduction: Hypogonadism is more prevalent in men with type 2 diabetes (T2DM) (25%‐40%) than in men without T2DM. Hypogonadism has been associated with poorer glycaemic outcomes and increased cardiovascular morbidity/mortality. We report a 14‐year follow‐up study to evaluate the influence of baseline testosterone level on T2DM outcomes. Research design and methods: A total of 550 men with T2DM underwent baseline total testosterone and dihydrotestosterone measurement by tandem mass spectrometry. Mean age of the men was 59.7 ± 12 (mean ± SD) years. Sex hormone‐binding globulin (SHBG) was measured and free testosterone estimated. Patients were followed up between 2002 and 2016. Mean follow‐up period was 12.2 ± 4 years using the Salford (UK) Integrated Health Records system. Results: Mean baseline total testosterone was 13.7 ± 5.8 nmol/L, and mean free testosterone was 245.7 ± 88.0 pmol/L. Mean for low total testosterone (<10 nmol/L) was 7.6 ± 2.0 nmol/L (n = 154) and 142 men had a free testosterone <190 pmol/L. During the 14‐year duration follow‐up, 22% of men experienced a myocardial infarction, 18% experienced a stroke, 11% developed angina, 14% underwent coronary revascularization. About 38% of the men initially recruited died. A lower total testosterone was associated with a higher body mass index (kg/m 2 ) at follow‐up: regression coefficient −0.30 (95% CI −0.445 to −0.157), P = 0.0001. The mortality rate was higher in patients with lower total testosterone compared to normal baseline total testosterone (5.0% vs 2.8% per year, P < 0.0001). A similar phenomenon was seen for dihydrotestosterone (4.3% vs 2.9% per year, P = 0.002) for normal vs low dihydrotestosterone) and for lower SHBG. Over the whole follow‐up period 36.1% (143/396), men with normal baseline testosterone died vs 55.8% (86/154) of hypogonadal men at baseline. In Cox regression, the age‐adjusted hazard ratio (HR) for higher mortality associated with low total testosterone was 1.54 (95% CI: 1.2‐2.0, P < 0.002), corresponding to a 3.2 year reduced life expectancy for hypogonadal T2DM men. Conclusion: Low testosterone and dihydrotestosterone levels are associated with higher all‐cause mortality in T2DM men. Hypogonadal men with T2DM should be considered as very high risk for cardiovascular events/death. Abstract : In this study, 550 men with type 2 diabetes (T2DM) underwent baseline total testosterone and dihydrotestosterone measurement by tandem mass spectrometry. Mean age of the men at baseline was 59.7 ± 12 (mean ± SD) years. We found that low baseline total/free testosterone and dihydrotestosterone levels were associated with higher all‐cause mortality in T2DM men over a 14‐year follow‐up period. Hypogonadal men with T2DM should be viewed as at very high risk for cardiovascular (CVD) death.